Analyzing the Process of Absorptive Capacity: A Case Study of Garment SMEs in Yogyakarta - Siregar, Dede Iskandar; Priyono, Anjar (Jurnal Manajemen Teknologi, 2020)
Abstract: Absorptive capacity is defined as the company's ability to identify, explore, and apply knowledge gained from the external environment into the form of services. Previous studies examined this generally put forward the role of R&D and leadership authority to neglect the natural process of absorptive capacity. As a knowledge process, its natural process unseparated from the involvement of all parties in the company (including employees). This study aims to analyze the absorptive capacity process in Gramen SMEs located in Yogyakarta with its characteristics that still prioritize business practices based on traditional approaches and local wisdom. By adopting a qualitative based on case studies, it found that the process of absorbing information generally carried out through informal interactions with customers and various communities. It is also confirmed that each stage of absorptive capacity does not always flow linearly, and the intensity of the absorption holds by companies determined by innovations required and the characteristics of the company.Keywords: Absorptive capacity; exploration; transformation; exploitation; innovation capability.Abstrak: Daya-serap diartikan sebagai kemampuan mengidentifikasi, eksplorasi dan menerapkan pengetahuan eksternal ke dalam bentuk produklayanana. Studi terdahulu yang mengkaji ini umumny mengedepankan peran R&D dan otoritas pimpinan sehingga membuat proses natural kapastitas absorptive terabaikan mengingat aktivitas penyerapan pengetahuan tersebut tidak terlepas dari keterlibatan semua pihak di perusahaan (termasuk pegawai). Studi ini bertujuan menganaliais proses kapsitas absorptive pada UKM gramen yang berlokasi di Yogyakarta dengan karakteristiknya yang masih menerapkan bisnis berdasarkan pendekatan tradisional dan kearifan lokal. Dengan mengadaptasi pendekatan kualitatif studi kasus, maka ditemukan bahwa proses penyerapan informasi dilakukan umumnya melalui interaksi informal dengan pelanggan dan kelompok komunitas. Disini juga dikonfirmasi bahwa tahapan absorptive (indentifikasi, eksplorasi, implemnetasi) tidak selalu mengalir linear dan intensitas daya serap tersebut sangat ditentukan oleh kebutuhan inovasi dan karakteristik perusahaan.Kata kunci: Kapasitas absorptive, eksplorasi, transformasi, eksploitasi, kapabilitas inovasi.